Disruptions to agrifood value chains in fragile and conflict-affected states: Evidence from Myanmar - Goeb, Joseph; Minten, Bart; Aung, Zin Wai; Htar, May Thet; Sabai, Moe; Syntb, Kham Nang Lun; Zu, A Myint; Mahrt, Kristi (Brill, 2026)
Agrifood value chains (AVCs) play crucial roles in food security in fragile and conflict-affected economies where there are widespread challenges and disruptions to business operations, food access, and incomes. Yet, given these challenges, safe data collection is challenging in conflict-affected settings and, as a result, the evidence on the disruptions AVC businesses face is thin. In this paper, we rely on novel panel data from AVC businesses in Myanmar, one of 7 countries in the world with extreme conflict. This short paper documents the disruptions experienced by businesses at several levels of the food supply chain, including farmers, input retailers, crop traders, rice millers, and food vendors. We also provide evidence on the implications for prices by analyzing price changes over this period: farm input and sales prices using farm survey data, food retail using data from food vendors, and dietary cost estimates combining consumption and price data. Our results highlight vulnerabilities in food supply chains in fragile and conflict-affected settings. Potential opportunities to strengthen food supply chains in such settings include ensuring access to banking and financial services; minimizing transportation disruptions to mitigate widening gaps between producer and consumer prices; and maintaining access to fuel and electricity as well as cellphone internet networks. Efforts to support these areas could stabilize food availability and reduce food prices, while also increasing farm-gate shares of food prices thereby supporting rural incomes.